(untitled) (Journal of Bangladesh College of Physicians and Surgeons, 2015)
A prospective study was done in the Department of Obstetrics & Gynaecology, BSMMU, Dhaka from January 2006 to December 2006. Hundred cases were studied during this period. The patients admitted for hysterectomy operation were divided into group A and group B. In group A 50 patients received prophylactic injectable 1 gm ceftriaxone, 500 mg metronidazole and 80 mg gentamicine one hour before operation. In group B 50 patients received conventional antibiotic comprising ciprofloxacin for 7 days (both I.V and Oral), metronidazole for 5 days (both I.V and oral) and gentamicine for 3 days (I.V / I.M). After fulfilling the inclusion and exclusion criteria the patients were randomly assigned to receive either parenteral loading dose of 1 gm Ceftriaxone, 500 mg Metronidazole and 80 mg Gentamicine (Group-A) pre-operatively or conventional dose of antibiotic (Group- B). Relevant careful clinical records and data were kept on predesigned proforma. Incidence of post-operative complications, operative time and hospital stay were recorded for each patient. Data was analyzed using SPSS program with the consultation of the statistician. Because of nature of the analysis, only chi-squire(X2) test was applied. Most of the patients (64% in Group-A and 67% in Group-B) were from low socio-economic class. Significant number of patients were anaemic (Hb% between 50-55%) and duration of operation was within 60-89 minutes in most of the cases. There were 3(6%) post operative wound infection in Group- A and 2(4%) post operative wound infection in Group-B after abdominal hysterectomy. 1 patient of Group-A and 1 patient of Group-B developed wound infection after vaginal hysterectomy operation. So, there was no significant difference in post-operative wound infection between Group- A and Group-B. Length of post-operative hospital stays in both groups were within 5-9 days (Group-A 90% and Group- B 92%). The study demonstrates that there is no significant difference regarding surgical outcome between Group-A and Group-B. Moreover the patient of Group-A needs antibiotic cost only Tk. 220 and Group-B needs of about Tk. 640, so that it saves about Tk. 420 which supports the economic benefits for Group-A and cost effectiveness. J Bangladesh Coll Phys Surg 2014; 32: 149-152